Optimization models for clustering of solid waste collection process. Issue 12 (2nd December 2021) - Al-Refaie, Abbas; Al-Hawadi, Ahmad; Fraij, Saja
Abstract : In Jordan, the waste collection process incurs high transportation and operation costs. The main reasons for the high transportation costs are inefficient clustering and poor routing systems. In response, this research proposes a mathematical model for optimal clustering of garbage containers or bins (referred to as customers) for solid waste collection. The model's objective function is to define the customers of each cluster such that the transportation costs within each cluster and between the hubs and depots are minimized, and the satisfaction of the clusters' demand mean and variance is maximized. The optimization model was illustrated on solid waste collection for 20 customers, where the results showed that the proposed model is found to be effective in optimizing the waste collection process. In practice, this approach can be utilized in waste management for planning waste collection processes with minimal transportation costs while maximizing operational capacity.